Experimental Tests and Analytical Modelling of a Scaled Isolated Structure on Sliding and Elastomeric Bearings - Fabio Mazza; Alfonso Vulcano (Advances in Materials Science and Engineering)
The main purpose of this study, which was conducted within the framework of a DPC-ReLUIS research project, was to investigate the behaviour of a scaled isolated structure equipped with an in-parallel combination of steel-PTFE sliding bearings and elastomeric bearings (HDRBs). For this purpose, dynamic tests on shaking table were carried out at the Laboratory of the Department of Structures for Engineering and Architecture of the University of Naples Federico II, Italy. An available prototype steel framed structure was used as a superstructure. A further objective of this study was to evaluate the reliability of different analytical models of the isolation system, commonly used, in order to adequately simulate the dynamic response of the isolated structure. The effectiveness of the isolation system was evaluated comparing the experimental response of the isolated structure with the numerical response of the fixed-base structure.